Hidrólise subcrítica de biomassas residuais de nogueira-pecã: caracterizações físico-química, morfológica e obtenção de açúcares redutores - Santos, Maicon Sérgio Nascimento dos (2020)
In this study, different pecan biomasses, such as husks, leaves, stalks and shells were submitted to hydrolysis by subcritical water (SWH), which resulted in a hydrolyzed solution rich in reducing sugars. The assays were carried out in a multipurpose unit located at the Laboratory of Agroindustrial Processes Engineering (LAPE) and belonging to the Universidade Federal de Santa Maria (UFSM), Campus Cachoeira do Sul. This unit contains a 50 mL hydrolysis reactor heated by thermal resistance, sensors and controllers of temperature, flow and pressure, once different conditions were considered for this study. For the assays, the variables temperature (180, 220 and 260 ºC), water/ solids mass ratio (R) (15 and 30 g water/ g initial biomass, corresponding to the flow rates of 20 and 40 mL/min, respectively) and reaction time (0.5 to 15 minutes) were considered. The pressure used was 30 MPa. Several responses were analyzed, such as yields of reducing sugars by UV spectrophotometry, sugar contents and inhibitors by high performance liquid chromatography (HPLC), and morphological characterization of the different biomasses by scanning electronic microscopy (SEM), Fourier-transform infrared spectroscopy (FT-IR) and thermogravimetric analysis (TGA). Regarding the pecan husks biomass, the results showed the highest yield of 26.5 g/ 100 g biomass in 220 ºC and R of 15 g water/ g biomass (220 ºC and R - 15, referring to the flow rate of 20 mL/min). For leaves and stalks, the highest yield, 26.3 g/ 100 g biomass, was found in the conditions of 260 ºC and R of 15 g water/ g biomass (260 ºC and R - 15, flow rate of 20 mL/min). For shells, the highest yield of 27.1 g/ 100 g biomass was found in 220 ºC and R of 15 g water/ g biomass (220 ºC and R - 15, flow rate of 20 mL/min). The analysis of HPLC hydrolysed solutions showed the presence of arabinose, cellobiose, glucose and xylose, as well as furfural and hydroxymethylfurfural. SEM analysis showed the rupture of the structure of fresh materials and the increase of superficial microstructures in the biomass. According to the TGA analysis, mass changes in the residues were observed different thermal conditions. Finally, FT-IR analysis expressed the identification of different components of the biomasses, comprehending the contents of cellulose, hemicelluloses and lignin.